The Use of Lubricants for Massage: Historical Overview - Alexey N. Voskresenskii; Mikhail A. Eremushkin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
The paper provides a historical analysis of the main teaching aids, both Russian and foreign, which influenced the formation of modernclassical massage techniques on the use of lubricants in the process of massage procedures. The research assessment section includedmainly Russian-language publications of the XX century. The transformation of ideas from the complete acceptance of various means toimprove the sliding of the hands of massage therapists during the massage procedure, to the complete rejection of their use, is noted.Aim. To prepare a literature review using Russian and foreign sources and present the data of modern research on the use of means toimprove the sliding of the massage therapist's hands in massage.Conclusion. Having analyzed the sources under study, we formed an opinion that most medical massage techniques should beperformed without the use of additional agents that improve the slip of the massage therapist's hands. However, only the clinicaljudgement expressed in the studied works is insufficient for the final solution of this problem, and clinical studies involving specialistsof related specialties (medical chemists, pharmacologists, etc.) are required.